Synergies of dark tourism, future trends and tourism education: a dialogue with Professors John Lennon and Ian Yeoman - Rodney Westerlaken; John Lennon; Ian Yeoman (Research in Hospitality Management)
This edited transcript documents a dialogue between Rodney Westerlaken, Editor-in-Chief of Research in Hospitality Management, and Professors John Lennon and Ian Yeoman, which took place as part of the Hotel Management School Leeuwarden’s celebration of World Tourism Day. The conversation explores the multifaceted dimensions of dark tourism, its future trends and its place in tourism education. The dialogue offers valuable insights into the motivations behind dark tourism, the impact of technology on visitor behaviour and the future challenges and opportunities in the tourism industry. Furthermore, it underscores the significance of interdisciplinary approaches in tourism research and education.